2020
DOI: 10.1016/j.ajp.2020.102083
|View full text |Cite
|
Sign up to set email alerts
|

Study of knowledge, attitude, anxiety & perceived mental healthcare need in Indian population during COVID-19 pandemic

Abstract: Novel Corona Virus Disease originating from China has rapidly crossed borders, infecting people throughout the whole world. This phenomenon has led to a massive public reaction; the media has been reporting continuously across borders to keep all informed about the pandemic situation. All these things are creating a lot of concern for people leading to heightened levels of anxiety. Pandemics can lead to heightened levels of stress; Anxiety is a common response to any stressful situation. This study attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

157
1,770
27
135

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,870 publications
(2,089 citation statements)
references
References 14 publications
157
1,770
27
135
Order By: Relevance
“…This survey received a total of 586 valid responses from endodontists across India during the study period. Of them 311(53.07%) were males and 325(55%) of the respondents belonged to the age group of [25][26][27][28][29][30][31][32][33][34][35] years. Predominantly the endodontists practiced in urban area(64%), engaging in solo practice(13.14%), private & group practice along with consultations (PSPC/GP-23.21%), only consultations(8.02%) and academics along with clinical practice(27.65%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This survey received a total of 586 valid responses from endodontists across India during the study period. Of them 311(53.07%) were males and 325(55%) of the respondents belonged to the age group of [25][26][27][28][29][30][31][32][33][34][35] years. Predominantly the endodontists practiced in urban area(64%), engaging in solo practice(13.14%), private & group practice along with consultations (PSPC/GP-23.21%), only consultations(8.02%) and academics along with clinical practice(27.65%).…”
Section: Resultsmentioning
confidence: 99%
“…There was a perceived mental healthcare need in at least 80 % of participants. (Roy et al, 2020) A study among Chinese HCW exposed to COVID-19 patients reported distress(75%), depression(50%), anxiety(45%), and insomnia(34%). Till date, the psychological stress perception due to COVID19 has not been assessed among Indian endodontists though they fall under high-risk group for this infection.…”
Section: Lock Down Backgroundmentioning
confidence: 99%
“…37 According to our results internet abuse was also associated to sleep problems and younger age. Roy et al, 20 found that, in Indian population, sleep difficulties, paranoia about acquiring COVID-19 infection and distress related to social media use were reported in 12.5 %, 37.8 %, and 36.4 % participants, respectively. The negative impact of internet abuse on both sleep duration and sleep quality has been previously described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Due to the sudden onset of COVID-19, few studies have explored the effects of SARS-COV-2 on mental health. 14,20,21 To our knowledge there are no studies in Latin American countries that have explored how this pandemic may increase internet addiction, and its relationship to triggering anxiety and depression in the general population. We believe that a comprehensive management of the pandemic is essential, not only focusing on the physical aspects and infected patients, but also on mental health , which can be directly reflected in ideas, emotions, and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three themes, pandemic related knowledge was most studied, followed by practices and attitudes (Tables 2-4). In the knowledge domain, symptoms (13,14,16,, transmission (14, 16, 22, 23, 25-29, 31-34, 37-49, 51, 52, 55-57, 59-78) and incubation period of the virus (16, 23, 26-28, 32, 37, 38, 41, 42, 46-50, 52-57, 59-64, 66-69, 78); management and treatment options (14, 16, 22-24, 26, 27, 29, 37, 39-43, 46, 48-51, 55, 56, 58, 60, 62, 64, 66-70, 78, 79); and clinical outcomes associated with infection (13, 16, 23-27, 29, 34, 37, 38, 40, 48, 50-52, 55, 56, 59, 61, 63-67, 69, 74-76, 78-81); high risk populations for infection (16, 23, 26, 27, 29, 37, 39-41, 48, 49, 55-59, 63, 65, 67, 68, 72, 78, 79); availability of vaccine (16, 29, 37, 39, 40, 42-44, 48, 52, 55, 56, 58, 60-63, 65, 68, 70, 74-76, 79); role of hand hygiene (14, 16, 24, 25, 28, 29, 42, 43, 45, 47, 48, 50, 52, 55-58, 60, 64, 66, 69-71, 82, 83) was most studied for medical and non-medical staff. (Table 2) For medical related populations specifically, knowledge about epidemiology (29, 37, 39, 42, 44, 53, 58, 59, 61-63, 65, 66, 78, 79) and diagnosis of infection (16, 46, 48, 49, 55, 56, 58-63, 67, 76) were also frequently evaluated.…”
Section: Themes Identified From Items Used In Health Literacy Questiomentioning
confidence: 99%